Evaluation of two-port laparoscopic ovariectomy in queen cats - Puniya, Meena; Kumari, Anita; Bishnoi, P.; Jhirwal, S.K.; Tanwar, Mahendra; Jyoti; Sharma, M.L.; Patwa, Ruchi; Kumari, Anita (Indian Journal of Veterinary Surgery, 2026)
Two-port laparoscopic ovariectomy was performed on eight healthy female cats. The anaesthesia was induced with midazolam and ketamine, and maintained with isoflurane. During the surgical procedure, the abdominal cavity was insufflated with CO2 and pressure of 8-10 mmHg was maintained, a 5 mm trocar-cannula assembly was inserted cranial to the umbilicus for insertion of telescope. A second 3 mm port was inserted caudal to umbilicus. Firstly one of the ovaries was grasped with the help of 2.5 mm Kelly’s forceps and pulled toward abdominal wall and fixed by transabdominal suture, and the ovarian pedicle and utero-tubal junction was cauterized and resected. The same procedure was followed for the other ovary. Once both ovaries were free, the transabdominal suspension suture was released and the ovaries were exteriorised from the abdomen. The incision site was sutured routinely. Intraoperative subcutaneous emphysema was observed in 2 cases, but no complication was recorded postoperatively. The two-port laparoscopic ovariectomy was found minimally invasive, safe, cosmetic and required less postoperative care.